PEMBANGUNAN DAERAH KALIMANTAN BARAT PASCA KRISIS EKONOMI - Panggabean, Meiran (Fakultas Ekonomi dan Bisnis, UNTAN, 2011)
Regional development in West Kalimantan faces not only economic problems but also nature and social ones, especially in 1997 as monetary crisis hit the indonesian economy. During the last ten years, started from unfavorable condition with a negative economic growth of -4,72%, improved economic growth had been succesfully achieved. West Kalimantan